NOVEL STUDY FOR CHEMICAL COMPOSITION OF AL-AHDAB CRUDE OIL - Tariq A. Al-Ani; Mohsin O. Mohammed; Abrahim H. Farhan (مجلة جامعة الانبار للعلوم الصرفة, 2017)
Thisn research included determination of chemical composition of al-ahdaab crude oil (kute- Iraq) using liquid – solid chromatography. The current researched included to separation the component of crude oil by column chromatography was packing with alumina (AL2O3) as a stationary–phases and several solvent as a mobile phase. . The results of crude oil fractionations were 17.01% Asphaltene, 82.99% Maltene, which separated to (Paraffinic) (saturated) 44.11%, Aromatic 30.11% and Resin 4.20%. Crude oil fractionation were characterized using Nuclear Magnetic Resonance H1NMR and Fourier Transform Infrared Spectrometer FT-IR to determine the chemical composition of each part, which is that represents the first study and a novel results. This study also clarified the paraffinic compounds are represented the main part of materials in crude oil composition.